Desempenho do sorgo BRS 716 como cultura energética para produção de biogás: monodigestão e codigestão com dejeto suíno - Lazaroto, Ana Claudia (2025)
Biogas, produced through the anaerobic digestion of organic substrates, emerges as a promising solution to meet the growing energy demand in a renewable and sustainable manner. The sources for biogas production are diverse, with a significant portion originating from residues such as swine manure. However, due to the increasing demand in recent years associated with productivity needs, the anaerobic digestion of energy crops has demonstrated several advantages. Among these, sorghum stands out as it does not compete for arable land with food crops, given its ability to thrive in low-fertility soils and its resistance to climatic adversities and water stress. The Brazilian sorghum cultivar BRS 716 is particularly noteworthy for its high fresh biomass yield, optimizing land use and reducing pressure on new agricultural areas. Nevertheless, literature reports indicate that this substrate is susceptible to inhibition due to the accumulation of volatile fatty acids (VFAs). Thus, this study aims to investigate the biogas production potential of sorghum in Continuous Stirred Tank Reactors (CSTR), operated under both mono-digestion and co-digestion with swine manure. The reactors were inoculated identically, fed with the same sorghum sample, and operated at 37°C with an agitation regime of 60 rpm. The experiments were conducted by gradually increasing the organic loading rate (OLR) of sorghum, starting at 0.5 kgvs m-3·d-1 up to (include the maximum loading). The monitored parameters included pH, volumetric biogas production, gas composition (CH4 and CO2), the intermediate-to-partial alkalinity ratio (IA/PA), VFA concentration, and volatile solids (VS). The results indicate that sorghum mono-digestion remained stable up to an OLR of 2.5 kgvs m-3·d-1, with methane yield and productivity of 200.73 LNCH4 kgvs -1 and 0.50 LNCH4 L-1reactor d-1, respectively. However, when the OLR was increased to 3.0 kgvs m3 ·d-1, propionic acid accumulation occurred, raising the FOS/TAC to 1.56 gHAc.gCaCO3-1, which impaired system buffering and negatively impacted biogas and methane production. In co-digestion with swine manure, no inhibition due to VFA or ammonia accumulation was observed. This system demonstrated greater operational flexibility, operating at an OLR 2.5 times higher than mono-digestion, reaching 6.21 kgvs m-3·d-1, resulting in a methane productivity of 1.11 LNCH4 L-1reactor d-1 and a yield of 179.16 LNCH4 kgvs -1. Microbial analysis revealed differences between the systems, where Methanosaeta was more abundant in mono-digestion, whereas Methanosarcina predominated in co-digestion, indicating distinct microbial adaptations associated with the substrates. Therefore, it is concluded that the BRS 716 cultivar exhibits high potential for biogas production, particularly due to its high biomass yield, which translates into greater methane yields per planted area. Sorghum mono-digestion is viable up to an OLR of 2.5 kgvs m-3·d-1; however, co-digestion with swine manure stands out as it offers significant advantages for achieving higher OLRs and increased methane production.